IDENTIFIKASI DAN POPULASICACING TANAH DI EKITAR LUBANG RESAPAN BIOPORI (LRB) YANG DIISI MEDIA LIMBAH KULIT BUAH KAKAO - Hasmah Hasmah; Annawaty Annawaty; Fahri Fahri (Biocelebes, 2017)
The purpose of this study is to identify the earthworm and how population earthworm in Biopore Absortion Holesfilled with cocoa pod waste. The study was conducted from April to August 2015 in the Sibonu Village, Sigi District Central Sulawesi province. Samples are preserved into alcohol series i.e 30%, 50%, and 70% before stored into alcohol 70 % for the pickling and identification process. Sample identification was executed at Laboratory of Biology, Faculty of Basic Sciences, Tadulako  University, Palu using identification key by Sims and Easton (1972) and Easton (1979). There are only one species found in the field namely Planapheretima sp. and earthworm juvenile which is belongs to family Megascolecidae. The result showed that there was one species is Planapheretima sp. and other individual are still in the juvenile phase of the family Megascolecidae of subgenus Planaheretima. The highest population density of earthworm is the biopore absortion holes 3 (cocoa pod waste), compared to the biopore absortion holes 1-2 (cocoa pod waste), K+ (without cocoa pod waste) and K- (without biopore absortion holes).